경도가 높은 촉성재배용 딸기 ‘하이베리’ 품종 육성 - 이인하(In-Ha Lee); 장원석(Won Suk Jang); 김태일(Tae Il Kim); 김현숙(Hyun Sook Kim); 남명현(Myeong Hyeon Nam); 이희철(Hee Chul Lee); 이병주(Byung Joo Lee); 오상근(Sang-Keun Oh) (Weon'ye gwahag gi'sulji, 2021)
‘하이베리’ 품종은 충남농업기술원 딸기연구소에서 2018년도에 육성한 촉성재배용 신품종이다. 경도가 높아 과실 수출에용이하고, 봄철 고온기에도 품질이 유지되는 품종을 육성하기 위해 경도가 높은 ‘NS071608’ 계통을 모본으로 하고 맛과 향이좋은 ‘대왕’을 부본으로 하여 2013년에 인공교배를 실시하였다. 2014∼2017년 실생선발, 특성검정, 생산력검정을 거쳐 ‘논산12호’로 계통명을 부여하고, 2018년에 ‘하이베리’로 명명하였다. ‘하이베리’ 품종은 초형이 직립형이고 초세가 왕성하다. 잎은 진한 녹색이며, 엽육 두께가 두껍고 엽형은 타원형이다. 과실의 과형은 원추형이고 과색은 선홍색을 띤다. 정화방의 화수는13개이고 평균 과중이 16 g으로 대과형 품종이다. ‘하이베리’의 상품수량은 2,623 kg·10a-1으로 ‘설향’의 97% 수준이다. 화경장이 37 cm로 길며 화방이 기부에서 갈라지는 형태를 나타낸다. 과실 경도는 15.3 g·mm-2으로 ‘설향’의 11.7 g·mm-2보다 3.6g·mm-2 더 단단하고 봄철 늦게까지 수확이 가능하다. 당도는 10.1°Brix으로 ‘설향’의 9.5°Brix보다 0.6°Brix 높다. 병해충 저항성은 시들음병에 강하나 흰가루병과 점박이응애에 약한 편이다. A new strawberry (Fragaria×ananassa Duch.) cultivar ‘Highberry’ was developed by StrawberryResearch Institute of Chungcheongnam-do Agricultural Research and Extension Services forforcing culture in 2018. In order to breed a new cultivar that is favorable to export with high fruitfirmness and maintain the fruit quality during warm temperatures in the spring season, ‘Highberry’originated from a cross between an unreleased selection ‘NS071608’ (female parent) with highfirmness and ‘Daewang’ (male parent) with good taste and fragrance in 2013. In 2014－2017, it wasoriginally named ‘Nonsan No. 12’ by conducting seedling selection, growth characteristics andproduction trials in forcing culture, and it was renamed ‘Highberry’ in 2018. ‘Highberry’ shows anerect plant type and vigorous growth habit. The leaves are dark green and thick and the leaf shapeis elliptic. Fruits are conical type; fruit color is red. The first cluster of ‘Highberry’ has 13 flowers,and it is a large fruit size cultivar with an average fruit weight of 16 g. The marketable yield of‘Highberry’ was 2,623 kg·10a-1, which is 97% of that of ‘Sulhyang’. The flower stem length of‘Highberry’ was 37 cm long and is divided into two stems from the bottom. Fruit firmness of‘Highberry’ was 15.3 g·mm-2, which was 3.6 g·mm-2 higher than 11.7 g·mm-2 of ‘Sulhyang’ and canbe harvested until late spring. The soluble solids content of ‘Highberry’ was 10.1°Brix, which was0.6°Brix higher than that of ‘Sulhyang’. ‘Highberry’ is resistant to Fusarium wilt but susceptible topowdery mildew and two-spotted spider mites. KCI Citation Count: 1